Particle beams from laser-irradiated solids at ultrahigh intensities - Nerush, E.N.; Kostyukov, I.Yu. (Вопросы атомной науки и техники, 2013)
Laser-solid interactions at the intensity range 10²³…10²⁶ W cm⁻² and the plasma density about 10²⁴ cm⁻³ are studied by means of numerical simulations. This range of parameters is extremely important for various laser applications such as fast ignition, gamma-ray generation and ion acceleration, and will be reached by the next generation of intense laser facilities. An overview of the interaction regimes is given. З використанням чисeльного моделювання розглянуто взаємодію лазерних імпульсів інтенсивністю 10²³…10²⁶ Вт·см⁻² з плазмовим шаром густиною 10²⁴ см⁻³. Розглянута область параметрів надзвичайно важлива для майбутніх застосувань надпотужних лазерних систем, наприклад, для схем «швидкого підпалу», для генерації гама-квантів, позитронів та прискорених іонів. Наведено огляд різних режимів взаємодії, що відповідають різним значенням інтенсивності лазерного поля. С использованием численного моделирования рассмотрено взаимодействие лазерных импульсов интенсивностью 10²³…10²⁶ Вт·см⁻² с плазменным слоем плотностью 10²⁴ см⁻³. Рассмотренная область параметров чрезвычайно важна для будущих приложений сверхмощных лазерных систем, например, для схем «быстрого поджига», для генерации гамма- квантов, позитронов и ускоренных ионов. Дан обзор различных режимов взаимодействия, отвечающих различным значениям интенсивности лазерного поля.